A review of extraction, purification, structural properties and biological activities of legumes polysaccharides - Zhu, Yingying; Feng, Xuewei; Guo, Jianhang; Wang, Li; Guo, Xudan; Zhu, Xiangzhen (Frontiers in Nutrition, 2022)
In recent years, polysaccharides derived from legumes polysaccharides have aroused worldwide interests. Phytochemical and pharmacological studies have studied the physicochemical properties (emulsification, stability and foaming) and demonstrated the biological activities (immune regulation, anti-oxidation, anti-tumor, hypoglycemic, hypolipidemic and intestinal flora regulation) of legumes polysaccharides. Besides, it is reported that the extraction methods will affect the structure features of polysaccharides, thus further changing their physicochemical properties and biological activities. This review appraised the available literatures described the extraction, purification, structural characterization, biological activity and functional properties of legumes polysaccharides in recent years. It can provide useful research underpinnings and updated information for the development and application of related polysaccharides in functional foods and medicinal field.